New Prenylated Stilbenes and Antioxidant Activities of Cajanus cajan (L.) Millsp. (Pigeon pea) - Taslim Ersam; Sri Fatmawati; Dini Nur Fauzia (Indonesian Journal of Chemistry, 2016)
New Prenylated stilbene derivatives, 3-hydroxy-4-prenyl-5-methoxy-stilbene acid (1) and 5,4'-dihydroxy-3-methoxy-2-prenyl-stilbene (2) had been isolated from methanol extract of Cajanus cajan (L.) Millsp. (Pigeon pea), a member of family fabaceae. The aim of this present work was to evaluate its in vitro antioxidant activity using 2,2-diphenyl-1-picryhydrazyl (DPPH) radical-scavenging. Isolation of compounds was achieved by extraction (maceration) and chromatographic technique. The structures of the compounds were determined based on UV, IR, 1H-NMR and 13C-NMR spectra and also by comparing with the previously reported data. Antioxidant activities (IC50) of 1 and 2 were 413.68 μg/mL and 271.53 μg/mL, respectively.